2017
DOI: 10.56617/tl.3628
|View full text |Cite
|
Sign up to set email alerts
|

Landscape disruption or just a lack of economic benefits? Exploring factors behind the negative perceptions of wind turbines

Abstract: This paper provides new empirical evidence on the hypothesis that the perception of landscape disruption by wind turbines is a substantially subjective and relative matter. It is based on a survey involving nearly five hundred residents living in six different locations with operational wind turbines in the Czech Republic. Geographical and socioeconomic factors and sociodemographic characteristics that affect local community perceptions of landscape disruption are explored using correlations and a regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The survey results showed that wind turbines affected the visual quality; low-quality landscapes were perceived as improved and high-quality landscapes as degraded. According to Frantal et al [21], the influence of wind turbines on visual aspects of the landscape is highly dependent on the local environmental and socioeconomic context. In addition, annoyance from the visual presence of wind turbines may add to and even reinforce the noise-related annoyance (and vice versa).…”
Section: Perceptionmentioning
confidence: 99%
“…The survey results showed that wind turbines affected the visual quality; low-quality landscapes were perceived as improved and high-quality landscapes as degraded. According to Frantal et al [21], the influence of wind turbines on visual aspects of the landscape is highly dependent on the local environmental and socioeconomic context. In addition, annoyance from the visual presence of wind turbines may add to and even reinforce the noise-related annoyance (and vice versa).…”
Section: Perceptionmentioning
confidence: 99%